2018
DOI: 10.1177/2333392817749681
|View full text |Cite
|
Sign up to set email alerts
|

Transportation and Other Nonfinancial Barriers Among Uninsured Primary Care Patients

Abstract: Introduction:Nonfinancial barriers are frequent causes of unmet need in health-care services. The significance of transportation barriers can weigh more than the issues of access to care. The purpose of this cross-sectional study was to examine transportation and other nonfinancial barriers among low-income uninsured patients of a safety net health-care facility (free clinic).Methods:The survey data were collected from patients aged 18 years and older who spoke English or Spanish at a free clinic, which served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Regarding transportation, studies have found that the transportation system is essential to health care, 17 particularly in rural areas, and that lack of transportation is a major barrier to proper management of chronic conditions. 37,38 It has been reported that more than 3.6 million people in the United States miss nonemergency or needed medical care because of lack of transportation. 39 Nonemergency medical transportation has been suggested as a viable alternative to improve access to health care in certain groups, including vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding transportation, studies have found that the transportation system is essential to health care, 17 particularly in rural areas, and that lack of transportation is a major barrier to proper management of chronic conditions. 37,38 It has been reported that more than 3.6 million people in the United States miss nonemergency or needed medical care because of lack of transportation. 39 Nonemergency medical transportation has been suggested as a viable alternative to improve access to health care in certain groups, including vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…The differential accessibility of uninsured population to testing is the likely explanation for this nding. Uninsured people are more likely to experience poverty and have transportation di culties, therefore they may not be able to reach the few and distant COVID-19 testing sites 20 .…”
Section: Dcrmentioning
confidence: 99%
“…Delahunt et al (2018) also reported high rates of cancellations and no-shows were due to a lack of reliable transportation and the inability of clients to take time off work. Kamimura et al (2018) found that 20% of free clinic patients missed appointments due to transportation barriers and that this barrier negatively impacted general health. Inconsistent attendance of therapy appointments adversely impacts client outcomes, which may negatively affect client satisfaction with the student clinic.…”
Section: Sustaining a Pro Bono Clinicmentioning
confidence: 99%
“…The clinic was offered during normal business hours, which may have also limited the participation of community members who were unable to take time off from work (Kamimura, Panahi, Ahmmad, Pye, & Ashby, 2018).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation